EAU guidelines on urological trauma - (:unkn) unknown (ELSEVIER SCIENCE BV, 2005)
Purpose: To determine the optimal evaluation and management of genitourinary (renal, ureteral, bladder, urethral and genital) injuries by review of the world's literature on the subject. Methods: A consensus committee convened by the Health Care Office of the European Association of Urology (EAU) to summarize the literature concerning the diagnosis and treatment of genitourinary trauma. Results: Findings of 350 citations are reviewed. Conclusions: The genitourinary trauma literature still relies heavily on expert opinion and single-institution retrospective series. Future prospective trials of the most significant issues, when possible, might improve the quality of evidence that dictates practitioner behavior. This paper represents a 5000 word summary of the full 35,000 word report. Full text of this review is available online at http://www.europeanurology.com. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: trauma; renal injury; bladder injury; urethral injury; ureteral injury; genital injury; BLUNT RENAL TRAUMA; FRACTURE URETHRAL INJURIES; LOWER URINARY-TRACT; TERM-FOLLOW-UP; PELVIC FRACTURES; SURGICAL-MANAGEMENT; ABDOMINAL-TRAUMA; NONOPERATIVE MANAGEMENT; BLADDER RUPTURE; PROSTATOMEMBRANOUS URETHRA